2004
DOI: 10.1017/s0272263104262015
|View full text |Cite
|
Sign up to set email alerts
|

LEARNING CONTEXT AND ITS EFFECTS ON SECOND LANGUAGE ACQUISITION: Introduction

Abstract: Thirty years ago, Dell Hymes~1972! observed that knowing what goes on outside the school setting is necessary to understanding what goes on inside+ He noted further that "the key to understanding language in context is to start not with language but with context + + + @and then to# systematically relate the two"~pp+ xix-lvii!+ Recently, the importance of learning context has stirred debate within SLA circles, and two coexisting lines of research have contributed to the overall picture that researchers and peda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
132
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(149 citation statements)
references
References 21 publications
7
132
0
10
Order By: Relevance
“…Learning a language is the process of appropriating the cultural resources or voices of local communities in broad social contexts. It is impossible for language learners to be quarantined from the "real world" and considered as a set of asocial, amoral skills to be mastered; they are always shaped, produced, and consumed in relation to broader social and cultural conditions (Burr, 1995;Collentine & Freed, 2004;Wertsch, 1991). Herron's (1994) findings indicated that comprehension in a foreign language is facilitated by richness of context.…”
Section: Context and Language Learningmentioning
confidence: 99%
“…Learning a language is the process of appropriating the cultural resources or voices of local communities in broad social contexts. It is impossible for language learners to be quarantined from the "real world" and considered as a set of asocial, amoral skills to be mastered; they are always shaped, produced, and consumed in relation to broader social and cultural conditions (Burr, 1995;Collentine & Freed, 2004;Wertsch, 1991). Herron's (1994) findings indicated that comprehension in a foreign language is facilitated by richness of context.…”
Section: Context and Language Learningmentioning
confidence: 99%
“…Some of the theories I have examined and applied in the analysis and interpretation of data are the following: social capital theory (Portes, 1998;Putnam, 2000), social identity and L2 acquisition (Norton, 2013;Norton Pierce, 1995), sociocultural theory of language acquisition (Collentine & Freed, 2004;Duff, 2007, Lantolf, 2000, immigrant acculturation and integration theory (Ager & Strang, 2008;Berry, 1997;Phinney, 1996). The analysis of data based on these multiple theories is presented in Part C of the thesis from chapter nine to chapter 13.…”
Section: Figure 1 Cyclical Process Of Data Analysismentioning
confidence: 99%
“…Taking the perspective that the context has a "strong and traceable" (Spolsky, 1988) influence in language learning, this chapter will discuss how the framework of context and social relationship enables or limits the learners' investment and progress in acquiring English. Many SLA researchers have contended that although language learning is an individual process, it occurs in a specific social context and thus needs to be understood with reference to the sociocultural factors embedded in the given contexts (Collentine & Freed, 2004;Firth & Wagner, 1997;Norton Pierce, 1995;Spolsky, 1988).…”
Section: Chapter 11 Host Community Context and Language Learningmentioning
confidence: 99%
“…Ellis (1994) defines the learning context as "the different settings in which L2 learning can take place." While contextual factors do not figure in every SLA theory, the relationship between context and learning has been investigated frequently clac 63/2015, 9-41 de clercq and simoens: paralell learning 15 because the former has been observed to significantly influence linguistic outcomes of foreign language learning (Collentine & Freed, 2004;Ellis, 2008). Learning contexts have typically been characterized through distinctions such as second and foreign language learning, or naturalistic and classroom exposure, in the assumption that different types of learning and different learning outcomes underpin these dichotomies (Housen et al, 2011).…”
Section: The Language Learning Contextmentioning
confidence: 99%